2021
DOI: 10.33487/edumaspul.v5i2.1889
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Demotivating Factors on EFL Students in Online Learning

Abstract: Demotivation is a complex problem that many foreign language (FL) learners faced, and it is caused by a variety of factors including the teacher, poor self-esteem, and previous bad language learning experiences(BABA KHOUYA, 2018). This study aimed to understand the demotivating factors on EFL students in online learning. The participants of this study were three students of the third grade of senior high school in Karawang. This study used a qualitative case study design to address the research objectives. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Their intrinsic motivation in learning English could be related to their personal interest and future goals , in order to accomplish goals. Some previous studies found that technical factor is the most common demotivating factor (e. g., Agung & Surtikanti, 2020;Aikina & Bolsunovskaya, 2020;Maemunah et al, 2021;Muthuprasad et al, 2021), as online learning requires a lot of data internet/quota and high speed of internet connection but students often ran out of quota https://doi. org/10.33508/mgs.v50i2.4175 and had low internet speed, even often experienced blackout.…”
Section: Discussionmentioning
confidence: 99%
“…Their intrinsic motivation in learning English could be related to their personal interest and future goals , in order to accomplish goals. Some previous studies found that technical factor is the most common demotivating factor (e. g., Agung & Surtikanti, 2020;Aikina & Bolsunovskaya, 2020;Maemunah et al, 2021;Muthuprasad et al, 2021), as online learning requires a lot of data internet/quota and high speed of internet connection but students often ran out of quota https://doi. org/10.33508/mgs.v50i2.4175 and had low internet speed, even often experienced blackout.…”
Section: Discussionmentioning
confidence: 99%